Pendampingan Kegiatan EDM Dan ERKAM Madrasah Di Kecamatan Sangkapura - Mahfud , Muhammad; Rudianto, Rahmat (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The use of e-RKAM and EDM applications is a concrete effort in realizing more effective, efficient, transparent and corruption-free management of the education budget. The purpose of the Assistance Activities is to ensure that each madrasah is able to carry out and use EDM instruments in accordance with the guidelines, as well as develop a RKAM based on EDM results using the e-RKAM application with the aim of Assessing madrasah performance based on SNP, Mapping madrasah strengths, weaknesses, opportunities and challenges, Helping determine the priorities of programs and activities that are in accordance with the needs of the madrasah. In this mentoring, several methods were used, including: lecture method, The Question and Answer method, Discussion method, and Simulation and Practice Methods, which are used to demonstrate the use of the EDM and ERKAM Applications. The results of the mentoring Madrasas were able to carry out EDM according to the established guidelines and compile RKAM using the e-RKAM application and all madrasas stated that mentoring activities were very useful and EDM work could be completed more quickly and on time because if there were difficulties they could be asked directly